Environmental effects of ozone depletion and its interactions with climate change: progress report, 2007 - Andrady, A.; Aucamp, P.; Alkiviadis, B.; Ballare, C.; Bjorn, L.; Bornman, Janet; Caldwell, M.; Cullen, A.; Erickson, D.; de Gruijl, F.; Hader, D.; Ilyas, M.; et al. (Royal Society of Chemistry, 2008)
Since the first assessments in 1989, the complexity of the linkages between ozone depletion, UV-Bradiation and climate change has become more apparent. This makes it even clearer than before that we are dealing with long-term developments, which can be complicated by large year-to-year variability.